International Legal Basis for Preventing Vandalism - Natalia RAKSHA; Anna BORENSTEIN; Elena POZDNYAKOVA; Yulia VETCHINOVA; Natalia BARBASHOVA; Anastasia KOLMYKOVA (Communications of International Proceedings, 2021)
The purpose of this research is to consider problems of the criminal law struggle with vandalism and to study legislations of foreign countries in terms of establishing the responsibility for the attack on property intended for public use. It is noted that in contrast to the Russian legislation the legislator of foreign countries is more cautious about the collective name of actions consisting in the desecration of buildings, constructions, as well as damage of property in public places. A comparative analysis of the norms of Russian criminal legislation and the norms of criminal legislation of foreign countries in terms of regulation of the responsibility for committing acts of desecration of buildings or structures, as well as damaging the property shows that they have much in common. The difference in the number of cases consists of the object of infringement and penalties. Further, it is important to note that foreign legislators often give a clearer collective definition of the acts committed by the perpetrators. Besides, they give a detailed indication of the subject of infringement and so on. That is why the Russian legislator has something to pay attention to in terms of regulation of responsibility for committing acts of vandalism. Thus, the research of the social conditionality of establishing criminal responsibility for vandalism allows us to come to the following conclusions. Vandalism in its criminal-legal conception requires greater attention from society and the state. So, it seems quite reasonable to include a separate norm providing responsibility for desecration of buildings and constructions, damage of property in public transport or other public places in the Criminal Code of 1996. The reasons for the emergence of vandalism are the characteristics of economic development, political attitudes prevailing and opposing at different levels. However, the main causes of vandalism should be primarily sought in the microenvironment of the offender, the impact of which most commonly determines the formation of his personality. The microenvironment can include low legal consciousness of the society, low legal culture, and education levels; shortcomings in the activities of law enforcement agencies, accessibility of objects of encroachment to damage due to their design, inadequate attention to the equipment of streets, places of recreation and leisure activities. Despite all this, the norms of Russian and foreign legislation have a single goal – to establish the protection of public property from criminal attacks.
Keywords: Law; Society; Property; Responsibility.